BATAS AURAT PEREMPUAN - Nurmala HAK (An Nisa'a, 2012)
When conversing genitals problem, in syara' text by authoritative do not clearly and coherent mention boundary of women’s genitals (aurat). All sect of Moslem scholar  interpret it with tendency of each direct very barbed possible with reality of life that happened and expand. From coverage of entire relevant text with definition genitals (aurat), even from Al-Qur'an and also hadits still be common enough, so that coverage of text assumed legal for considering almost entire body of woman is genitals (aurat), in consequence there is tendency of discussion of about genitals (aurat) become limited to group of just woman. This article want to study farther how boundary of woman’s genitals (aurat) according to Islam concept.